2020
DOI: 10.1111/tmi.13413
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of child mouthing of faeces and fomites in Dhaka, Bangladesh (CHoBI7 Program)

Abstract: Objective To characterise childhood mouthing and handling behaviours and to assess the association between hand‐to‐object and object‐to‐mouth contacts and diarrhoea prevalence in young children in urban Dhaka, Bangladesh. Methods A prospective cohort study was conducted among 494 children under 5 years of age in Dhaka, Bangladesh. This study was nested within the randomised controlled trial of the Cholera Hospital‐Based Intervention for 7 Days (CHoBI7) mobile health (mHealth) program. The CHoBI7 mHealth progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…36,57 The association identified in our present study is likely because feces on the household compound contributed to fecal contamination of drinking water sources that are often illegal connections to the municipal water supply [58][59][60][61] and contributed to pediatric exposure to fecal pathogens through child mouthing behaviors. [13][14][15][16] High E. coli (> 100 CFU/100 mL) in source water was a significant risk factor for diarrhea in young children in this study. This finding are also consistent with previous studies that have found unimproved and unprotected water sources, which are more prone to fecal contamination, to be associated with pediatric diarrhea.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…36,57 The association identified in our present study is likely because feces on the household compound contributed to fecal contamination of drinking water sources that are often illegal connections to the municipal water supply [58][59][60][61] and contributed to pediatric exposure to fecal pathogens through child mouthing behaviors. [13][14][15][16] High E. coli (> 100 CFU/100 mL) in source water was a significant risk factor for diarrhea in young children in this study. This finding are also consistent with previous studies that have found unimproved and unprotected water sources, which are more prone to fecal contamination, to be associated with pediatric diarrhea.…”
Section: Discussionmentioning
confidence: 51%
“…[9][10][11][12] Geophagy, the consumption of soil, dirt, or mud, and child mouthing of feces and fomites have been associated with environmental enteropathy, diarrhea, and growth faltering in young children. [13][14][15][16][17] Previous studies have also identified unimproved drinking water sources, poor water storage practices, not treating drinking water in the home, lack of caregiver handwashing with soap, lack of caregiver awareness of hygiene practices,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 In addition, unsafe disposal of child feces can lead to fecal contamination in the household compound and diarrheal disease in young children. 35 Most recently, our cohort studies 16,19,21 in Bangladesh and the Democratic Republic of the Congo found child mouthing of contaminated fomites and feces was associated with diarrheal disease among young children in both rural and urban settings.…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17] Young children often put surfaces and objects from their environment in their mouth; this is a normal part of their development. 18 Several studies have demonstrated that geophagy-the consumption of soil, dirt, or mud-and child mouthing of feces, fomites, and contaminated hands, have been associated with EE, diarrhea, and growth faltering in young children 16,[19][20][21][22][23] The presence of feces on the household compound and improper waste disposal has been associated with childhood diarrhea. [24][25][26][27][28] Zoonoses can also cause diarrheal diseases among young children, 29 with domestic animals such as birds spreading fecal pathogens in the household environment.…”
Section: Introductionmentioning
confidence: 99%